Bibliometric analysis of the inflammation in diabetic cardiomyopathy - Zhu, Ning; Huang, Bingwu; Zhu, Liuyan (Frontiers in Cardiovascular Medicine, 2022)
Background Maladaptive inflammation is implicated in the development of diabetic cardiomyopathy (DCM). This study aimed to visually analyze the global scientific output over the past two decades regarding research on inflammation associated with DCM. Methods All relevant articles and reviews were retrieved in the Web of Science (WOS) Core Collection (limited to SCIE) using “inflammation” and “diabetic cardiomyopathy” as search terms. Articles and reviews published from 1 January 2001 to 28 February 2021 were collected. Visualization analysis and statistical analysis were conducted by Microsoft 365 Excel and VOSviewer 1.6.18. Results A total of 578 documents were finally selected for further analysis. The publications regarding inflammation and DCM increased gradually over approximately 20 years. The most prolific country was China, with 296 documents and the most citations (9,366). The most influential author groups were Lu Cai and Yihui Tan who were from the United States. The bibliometric analysis of co-occurrence keywords showed that inflammation in DCM is composed of numerous molecules (NF-κB, NLRP3 inflammasome, Nrf-2, TNF-α, protein kinase C, PPARα, TLR4, p38 mitogen-activated protein kinase, TGF-β, Sirt1, and AKT), a variety of cardiac cell types (stem cell, fibroblast, and cardiomyocyte), physiological processes (apoptosis, oxidative stress, autophagy, endoplasmic reticulum stress, hypertrophy, mitochondrion dysfunction, and proliferation), and drugs (sulforaphane, metformin, empagliflozin, and rosuvastatin). Conclusion Our bibliometric analysis presents the characteristics and trends of inflammation in DCM and shows that research on inflammation in DCM will continue to be a hotspot.